Resilience in Crisis: The Impact of HRM Practices on Job Performance and Emotional Exhaustion Among University Employees - Mirdin ZILIC; Mihaela Alexandra TUDOR (Eurasian Journal of Business and Economics)
Organizations worldwide, including universities, have been significantly impacted by the COVID-19 pandemic, which required swift adaptations in human resource management practices to maintain employee performance. This research examined the relationships between HRM practices, job performance, and the mediation of emotional exhaustion among university employees in the Western Balkans, reflecting on COVID-19 experiences. An online survey was conducted across public and private universities in the region, collecting 1,020 responses. The results showed a significant positive relationship between HRM practices and job performance. Furthermore, a significant negative relationship was found between HRM practices and emotional exhaustion. Despite predictions, the study did not confirm that emotional exhaustion mediates the relationship between HRM practices and job performance. This study emphasized how important HRM practices are to preserving job performance and reducing emotional exhaustion among university staff members during the COVID19 epidemic. The results highlighted the necessity of specialized HRM approaches that tackle the difficulties encountered by university staff, guaranteeing their welfare and continued productivity in times of emergency.